The forgotten habitats in conservation: early successional vegetation - Sandoval Vargas, Luis Andrés (2019)
Conservation efforts in terrestrial environments have focused on preserving patches of natural habitats and restoring disturbed habitats, with the main goal of transforming them into forests or habitats that resemble the original conditions. This approach tends to overlook the importance of conserving early successional vegetation (e.g., riverside vegetation, natural regeneration, young secondary forests), which often includes a large number of species (e.g., plants and animals) associated with or restricted to these habitats. In this paper we want to bring to attention the importance of preserving early successional vegetation, and to encourage scientists to investigate, e.g., the diversity, distribution, and species interactions occurring in these habitats. To address these goals, we focus on two main objectives: (1) to identify the common types of early successional vegetation in the Costa Rican Central Valley; and (2) to use some case studies to draw attention to the importance that such areas have as reservoirs of a large portion of the diversity unique to early successional stages. We first include an example to show the diversity of plants in small forest patches immersed in a large urbanized area. We provide general information on the insects that occur in early successional vegetation in urban areas, and in further detail examples of butterflies. Additionally, we provide examples of birds and mammals that are restricted to early successional vegetation, and how the reduction of this vegetation type affects species conservation. Finally, we encourage scientists to investigate these early successional habitats, particularly those species exclusive to early successional stages. Special attention should be paid to endemic species and those with a restricted distribution. Information of this type will make conservation of the diversity contained in these habitats possible.